Epidemiological profile and prognostic factors in patients with lung cancer - Trufelli,Damila Cristina (2016)
SUMMARY Objective: To describe the epidemiological profile of patients with lung cancer treated at a public tertiary referral hospital specializing in oncology, and to explore variables that may be related to the overall survival (OS) of these patients. Method: Data from the medical records of all patients with invasive lung cancer consecutively seen at the Oncology Department of Hospital Estadual Mário Covas between August 2008 and December 2013 were extracted. The information obtained was submitted to statistical analysis. Results: Of the total 210 patients, 39 were excluded from analysis due to lack of information in the medical record. The most common histological type was adenocarcinoma, representing 39.41% of the sample, followed by squamous cell carcinoma with 25.29% and small-cell carcinoma with 13.53%. Other histological types were responsible for the remaining 21.76%. There was a statistically significant association between Karnofsky performance status (KPS) ≤ 70%, palliative chemotherapy lines performed and stage at diagnosis, and OS. Additionally, administration of target therapy to patients with EGFR mutation was associated with significantly better overall survival. However, analysis of laboratory variables (hemoglobin, albumin and LDH) as possible prognostic factors for survival showed no statistically significant relationship. Among patients with stage III and IV, the median OS was 10.1 months. Conclusion: The risk factors for shorter OS were KPS score ≤ 70%, less than two lines of palliative chemotherapy, and stage III and IV at diagnosis. The implementation of CT screening for risk patients may allow earlier diagnosis of cases and improve these results.